2013
DOI: 10.17576/pengurusan-2013-39-04
|View full text |Cite
|
Sign up to set email alerts
|

Initial Returns of Shariah versus Non-Shariah IPOs: Are There Any Differences?

Abstract: This study examines a sample of 384 initial public offerings (IPOs) issued and listed on Bursa Malaysia from January 1999 to December 2008. The objectives of this study are to examine the difference in initial returns of Shariah versus non-Shariah IPOs and the factors that explain the initial returns of these IPOs. A matched sample of Shariah IPOs, which contains the same number of IPOs and share similar characteristics with the non-Shariah IPOs, is created to ensure a more compatible comparison. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…The study contributes to the existing theory on the signalling hypothesis concerning the IPO values in the aspects of the application of Trueman's (1986) signalling model in emerging market, specifically in Malaysia. The findings of this study justify the significant and signalling effect of growth opportunities that propel the aftermarket prices and firms market values, and eventually increase initial returns, which gives support on the positive relationship between growth opportunity and IPO underpricing that provided by Abdul-Rahim and Che-Embi (2013).…”
Section: Discussionsupporting
confidence: 62%
“…The study contributes to the existing theory on the signalling hypothesis concerning the IPO values in the aspects of the application of Trueman's (1986) signalling model in emerging market, specifically in Malaysia. The findings of this study justify the significant and signalling effect of growth opportunities that propel the aftermarket prices and firms market values, and eventually increase initial returns, which gives support on the positive relationship between growth opportunity and IPO underpricing that provided by Abdul-Rahim and Che-Embi (2013).…”
Section: Discussionsupporting
confidence: 62%
“…Based on the report by Mohd- Rashid et al (2018) from 2000 to 2014, the average value of IPO offer price was lower than the RM0.96. Abdul-Rahim and Che-Embi (2013) reported that this value was lower than RM1.11…”
Section: Analysis Of Resultsmentioning
confidence: 86%
“…These results therefore indicate that companies' IPO motivation in the Malaysian IPO market was to finance the future investment and future growth of assets. The current study is different from prior IPO studies in the Malaysian IPO market (Abdul-Rahim & Che-Embi, 2013;Jelic, Saadouni, & Briston, 2001), because it investigates the specific items that issuers disclose as the intended use of the IPO's proceeds and the amount allocated to each use. Therefore, this study uses the information in the prospectus to find out the intended use of the IPO's proceeds, rather than making use of accounting information in the annual report, which is regarded as expost IPO information.…”
Section: Introductionmentioning
confidence: 99%